2019
DOI: 10.1128/jvi.01984-18
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Promotes Replication of Influenza A Virus In Vitro

Abstract: Influenza A virus (IAV) infection could induce autophagosome accumulation. However, the impact of the autophagy machinery on IAV infection remains controversial. Here, we showed that induction of cellular autophagy by starvation or rapamycin treatment increases progeny virus production, while disruption of autophagy using a small interfering RNA (siRNA) and pharmacological inhibitor reduces progeny virus production. Further studies revealed that alteration of autophagy significantly affects the early stages of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 76 publications
2
63
0
2
Order By: Relevance
“…Some viruses, such as ZIKV and rotavirus require the process early in infection [43][44][45][46], whereas this is detrimental for others. Conversely, some viruses, such as influenza A virus induce autophagy late after infection to increase replication [47]. Finally, there are viruses in which autophagy does not appear to influence replication.…”
Section: Various Viruses Influence Autophagymentioning
confidence: 99%
“…Some viruses, such as ZIKV and rotavirus require the process early in infection [43][44][45][46], whereas this is detrimental for others. Conversely, some viruses, such as influenza A virus induce autophagy late after infection to increase replication [47]. Finally, there are viruses in which autophagy does not appear to influence replication.…”
Section: Various Viruses Influence Autophagymentioning
confidence: 99%
“…Although LC3 is not integrated into the budding IAV virions, it appears that the presence of LC3 at the plasma membrane is able to modulate viral envelope composition by remobilizing appropriate resources to the cell surface during budding, to assist in virion stability via unknown mechanisms. Apart from these mechanisms, Wang et al [47] suggested another possible molecular mechanism for M2 to assist IAV in evading the autophagy machinery, by involving the host factor heat shock protein 90a (HSP90AA1). HSP90AA1 is an essential chaperone that maintains PI3K/AKT activity by binding to AKT and interacting with PB2 to facilitate viral RNA synthesis, viral ribonucleoprotein (vRNP) nuclear import, and viral assembly [48][49][50].…”
Section: Orthomyxoviridaementioning
confidence: 99%
“…HSP90AA1 is an essential chaperone that maintains PI3K/AKT activity by binding to AKT and interacting with PB2 to facilitate viral RNA synthesis, viral ribonucleoprotein (vRNP) nuclear import, and viral assembly [48][49][50]. The authors found that in addition to colocalizing and interacting with LC3 in the perinuclear region, which results in enhanced vRNP export and infectious virion formation, M2 and NP also increased HSP90AA1 expression and regulated the AKT-mTOR pathway to mediate autophagosome accumulation [47]. Therefore, at early stages of infection, NP and M2 induced autophagy to facilitate viral RNA synthesis via increased levels of HSP90AA1 that bind to PB2 and by enhancing vRNP export through binding of NP to LC3.…”
Section: Orthomyxoviridaementioning
confidence: 99%
“…only presents in late stages (Supplemental Figure 2C). Wang et al reported that influenza virus can induce autophagosome accumulation and autophagy promotes replication of Influenza virus in turn (22). Pharmacological inhibition of autophagy could decrease influenza viral yields (23).…”
Section: Il-36g Promotes Apoptosis and Inhibits Autophagy In Lung Epimentioning
confidence: 99%